Father's Role: A Study of Fathers in Bandung - Sumaryanti, Indri Utami; Yuniar, Jannah (DAS Institute, 2022)
The research found that the father’s role was important in many aspects of children’s life. Father’s roles were viewed differently in several countries. According to the research conducted in a country that holds family tradition, the father figure became strong when the father had access to wealth. It can be concluded that material and financial aspects hold an important role. Another research found a different result in another country where fathers were viewed as neopatriarchal father, failed father, and father substituted by others. Bandung is a city that represented Sundanese family values and also represented diversity. Therefore, this research was aimed to investigate father’s roles based on their own perspectives. The subjects were 100 fathers in Bandung obtained by multi-stage sampling. The quantitative method was used to explain the role of the father, while the data collection method used was questionnaire. The data analysis used was descriptive statistics. This research concluded that there were 3 father’s roles that were viewed as important roles, i.e., father as a model, as a teacher, and as an encourager.